Hubungan Peran Perawat Dengan Kesiapsiagaan Menghadapi Bencana Alam Banjir Di Puskesmas Rawang Tahun 2025 - Mimi Rosiska; Sarni Yati; Reni Trevia; Laurensia (Universitas Sumatera Barat, 2025)
Nurses play a strategic role in flood disaster preparedness as they are the spearhead of health services in emergency situations, including providing initial aid, triaging victims, and maintaining continuity of services in the field. In addition to their clinical functions, nursing staff also play a role in educating the public regarding disaster prevention, mitigation, and management. This study aims to analyze the relationship between the role of nurses and flood preparedness at the Rawang Community Health Center in 2025. This quantitative study with a cross-sectional design involved 42 nurses as respondents using a total sampling technique. Data were collected through a questionnaire that had been tested for validity and reliability. The results showed that of the 42 respondents, 30 (71.4%) had a good role, and the majority (54.8%) were considered prepared to face a flood disaster. Meanwhile, of the 12 nurses with a lesser role (28.6%), half (26.2%) showed low preparedness. The Chi-Square statistical test produced a p-value of 0.000, indicating a significant relationship between the role of nurses and flood preparedness. These results emphasize the importance of increasing capacity and disaster training for nursing staff so that it can be consistently applied in daily service practices.